Respuesta :

Answer:

See below

Step-by-step explanation:

This is a reflection in the x axis ( the 2 ---> -2) and a translation up of 3 units  (The +3).

Answer:

Reflection on the x axis and vertical displacement 3 units up

Step-by-step explanation:

If we do [tex]y = f (x)[/tex] then the original function is:

[tex]f(x)=2x^2[/tex]

The transformed function is as follows

[tex]y=-2x^2+3[/tex]

Then we can see that the transformation that was made was:

[tex]y=-f(x) +3 = -(2x^2)+ 3=-2x^2+3[/tex]

In general, a transformation of the form:

[tex]y = -f (x)[/tex]

reflects the graph of f(x) on the x axis.

A transformation of the form

[tex]y = f (x) + k[/tex]

If [tex]k> 0[/tex] then transformation shifts the graph of f(x) k units up

Then the transformation was: reflection on the x axis and vertical displacement 3 units up